A Review on Synthesis, Properties, of Liquid Crystal Dendrimers - R. Jber, Nasreen; H. Ali, Zinah (Al-Nahrain Journal of Science, 2021)
This review provides brief information concerning with the dendrimer. The supramolecular organization of selected examples of liquid-crystalline dendrimers within lamellar, columnar and nematic phases is reported. It is shown that tuning of the mesomorphic structure can be achieved by an appropriate molecular design depending upon the chemical nature of the terminal mesogenic groups, dendritic core and dendrimer generation. The pseudospherical shape of a dendrimer arises from its structure, which consists of an internal region (the core) which is connected to repeating units constituting a radial branching pattern.